2000
DOI: 10.1007/bf02491020
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatographic separation of fluoroquinolone antibacterials used as veterinary drugs

Abstract: SummaryA liquid chromatographic method has been developed to separate a series of quinolones which are wiclely used as veterinary drugs: clanofloxacin, clifloxacin, enrofloxacin (and its metabolite ciprofloxacin), marbofloxacin, norfloxacin and sarafloxacin. Separation was performed by using an end-capped high-purily silica-based C8 column and a mobile phase consisting of acetonitrile-aqueous oxalic acid buffer solution. In order to establish the optimal conditions for an isocratic separation, a three-factor D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The sensitivity obtained by use of this CE method is similar to that obtained by liquid chromatography [1,3,5,6].…”
Section: Analysis Of Plasma Samplesmentioning
confidence: 55%
See 1 more Smart Citation
“…The sensitivity obtained by use of this CE method is similar to that obtained by liquid chromatography [1,3,5,6].…”
Section: Analysis Of Plasma Samplesmentioning
confidence: 55%
“…This kind of sample is characterized by its complexity and so must be treated before CE analysis by deproteinization [2], liquid-liquid extraction (LLE) [1,5], and/ or solid-phase extraction (SPE) [4,6], etc.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study [16], we reported the use of a mobile phase consisting of an AN-H20 mixture containing oxalic acid as a buffer for the separation of a series of 7-piperazinylquinolones, resulting in good peak symmetry. An analogous mobile phase was tested for the separation of FLU and OXO here.…”
Section: Chromatographic Proceduresmentioning
confidence: 99%
“…Most of them involve liquid chromatography with ultraviolet (LC-UV; Gigosos et al, 2000;Pecorelli et al, 2003;Bailac et al, 2004;Christodoulou and Samanidou, 2007), fluorescence (LC-FD;Eng et al, 1998;Hernández-Arteseros et al, 2000;Chu et al, 2002;EspinosaMansilla et al, 2005;Hassouan et al, 2007) or mass spectrometric detection (Van Vyncht et al, 2002;Toussaint et al, 2002Toussaint et al, , 2005aSchneider et al, 2005;Van Hoof et al, 2005;Hermo et al, 2006;Bailac et al, 2006;Rubies et al, 2007).…”
Section: Introductionmentioning
confidence: 98%